The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physrevb.90.125125
|View full text |Cite
|
Sign up to set email alerts
|

High-energy collective electronic excitations in layered transition-metal dichalcogenides

Abstract: We characterize experimentally and theoretically the collective electronic excitations in two prototypical layered transition-metal dichalcogenides, NbSe 2 and Cu 0.2 NbS 2 . The energy-and momentum-dependent dynamical structure factor was measured by inelastic x-ray scattering (IXS) spectroscopy and simulated by time-dependent density-functional theory. We find good agreement between theory and experiment, provided that Nb semicore states are taken into account together with crystal local-field effects. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…We note that exchange-correlation effects beyond RPA in this class of materials are not changing qualitatively the results[22,24].…”
mentioning
confidence: 54%
“…We note that exchange-correlation effects beyond RPA in this class of materials are not changing qualitatively the results[22,24].…”
mentioning
confidence: 54%
“…In 2H materials, on the other hand, due to the different splitting of the d orbitals, only the metallic states with d z 2 character are able to sustain collective excitations alone. The interband transitions between d states, in fact, strongly mix with the higher-energy transitions involving π and σ bands related to the p z and p xy orbitals of the chalcogen atoms, giving rise to the π + σ plasmon located at 8 eV [22]. This excitation (not shown) is present in 1T systems as well and is located at about 6.6 eV.…”
Section: A In-plane Loss Functionmentioning
confidence: 93%
“…Since in our preliminary tests we found that in the small-energy range considered here the effect of f xc in the adiabatic local-density approximation is negligible (see also Refs. [20] and [21]), in the following we will consider results obtained in the random-phase approximation (RPA) in which f xc = 0 and that has already been proven to be sufficient to obtain a good agreement with available experimental data [18,19,22]. This approximation has been used to evaluate the loss function of single-sheet TMD as well since previous works on graphene and single-wall carbon nanotubes, see e.g.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Layered transition-metal dichalcogenides (TMDs) are an intriguing family of materials that span a broad range of physical properties and have been extensively studied for applications in catalysis, tribology, electronics, photovoltaics, and electrochemistry. [11][12][13][14] Through exfoliation, layered TMDs with strong covalent inplane bonds and weak van der Waals-like coupling between layers, can be made into single-and few-layer flakes. [15][16][17][18][19][20][21] With the relative fabrication easiness compared to one dimensional materials, 2D materials are expected to have a significant impact on next-generation nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%